Histochemical study of the endometrium in infertile women - Mezzadra, José (2015)
And endometrial clinical study of 43 patients was made sterile. Morphological and histochemical study was conducted on approximately 400 prepared investigated glycogen, mucus, alkaline phosphatase and acidic mucoproteins mucopolisacáricos. In 21 cases or 49% is abnormal endometrial picture was observed and 66% of them corresponded to an inadequate secretion phase and the remaining 34% anovulatory cycles. It is noted that the phase endometrium with incomplete secretion are more abundant than in endometrium proliferation. Glycogen, mucopolysaccharides, mucoproteins appeared in quantities and normal distribution if they relate to the stages of the cycle (Table No. 9). Alkaline phosphatase glands and vessels was frankly groups decreased in infertile women with incomplete cycles. This finding does consider the need to study with equal attention the amount of glycogen and mucus, and further studies will be necessary to clarify the true meaning of this endometrial hypophosphatasia. The comprehensive study of the endometrium in the barren by histochemical techniques can give us a better idea of their ability nesting.